Pengembangan Model Economic Production Quantity (EPQ) dengan Sinkronisasi Demand Kontinu dan Diskrit Secara Simultan - Nurike Oktavia; Henmaidi; Jonrinaldi (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2016)
The most popular inventory model to determine production lot size is Economic Production Quantity (EPQ). It shows enterprise how to minimize total production cost by reducing inventory cost. But, three main parameters in EPQ which are demand, machine set up cost, and holding cost, are not suitable to solve issues nowadays. When an enterprise has two types of demand, continue and discrete demand, the basic EPQ would be no longer useful. Demand continues comes from a customer who wants their needs to be fulfilled every time per unit time, while the fulfillment of demand discrete is at a fixed interval of time. A literature review is done by writers to observe other formulation of EPQ model. As there is no other research can be found which adopt this topic, this study tries to develop EPQ model considering two types of demand simultaneously.